Evaluating Nursing Electronic Training Course of Neonatal Stabilization Before Transport - Maliheh Kadivar; Nayma Seyedfatemi; Maryam Sadat Soltandoost Nari; Abbas Mehran (Journal of Client-centered Nursing Care, 2017)
Background: Stabilization of the vital components of neonates before the transform significantly affects their response to treatment. This study aims at evaluating the effects of electronic learning on neonatal stabilization before transform on nurses’ knowledge. Methods: The current quasi-experimental, case-control study of e-learning of neonatal stabilization before the transform was conducted in 10 weeks in 2015 on nurses and midwives taking care of newborn infants. Three teaching hospitals in Tehran, Iran, were randomly selected and samples were selected using the convenience sampling method. The samples were allocated to two groups, intervention (n = 40) and control (n = 41). Data collection was conducted using two questionnaires on demographic information and a researcher-made multiple-choice questionnaire to assess the level of knowledge. Collected data were analyzed with SPSS version 18 using paired t and Fisher exact tests, P < 0.05 was considered as the level of significance. Results: In the current study, both the intervention and control groups were homogeneous in terms of demographic characteristics. A significant difference was also observed in the knowledge level of the intervention group between the pre- and post-intervention measures (P < 0.001), but the same difference in the control group was insignificant (P = 0.16). There was also a significant difference between the study groups in terms of pre- and post-intervention comparisons (P < 0.001). Conclusion: E-learning of neonatal stabilization before transform improved the knowledge of participants in the intervention group. It seems that implementation of the same training courses at large scales can improve the therapeutic results of transformed neonates.